Use of cannabis during pregnancy and birth outcomes in an Aboriginal birth cohort: a cross-sectional, population-based study. Issue 2 (23rd February 2016) - Brown, Stephanie J; Mensah, Fiona K; Ah Kit, Jackie; Stuart-Butler, Deanna; Glover, Karen; Leane, Cathy; Weetra, Donna; Gartland, Deirdre; Newbury, Jonathan; Yelland, Jane
Abstract : Objectives: Indigenous women continue to experience rates of stillbirth, preterm birth and low birth weight, two to three times higher than other women in high-income countries. The reasons for disparities are complex and multifactorial. We aimed to assess the extent to which adverse birth outcomes are associated with maternal cannabis use and exposure to stressful events and social health issues during pregnancy. Design/setting: Cross-sectional, population-based survey of women giving birth to Aboriginal babies in South Australia, July 2011–June 2013. Data include: maternal cannabis use, exposure to stressful events/social health issues, infant birth weight and gestation. Participants: 344 eligible women with a mean age of 25 years (range 15–43 years), enrolled in the study. Participants were representative in relation to maternal age, infant birth weight and gestation. Results: 1 in 5 women (20.5%) used cannabis during pregnancy, and 52% smoked cigarettes. Compared with mothers not using cannabis or cigarettes, mothers using cannabis had babies on average 565 g lighter (95% CI −762 to −367), and were more likely to have infants with a low birth weight (OR=6.5, 95% CI 3.0 to 14.3), and small for gestational age (OR=3.8, 95% CI 1.9 to 7.6). Controlling for education and other social characteristics, including stressful events/social health issues did not alter the conclusion that mothers using cannabis experience a higher risk of negative birth outcomes (adjusted OR for odds of low birth weight 3.9, 95% CI 1.4 to 11.2). Conclusions: The findings provide a compelling case for stronger efforts to address the clustering of risk for adverse outcomes in Aboriginal and Torres Strait Islander communities, and point to the need for antenatal care to address broader social determinants of adverse perinatal outcomes. Integrated responses—collaboratively developed with Aboriginal communities and organisations—that focus on constellations of risk factors, and a holistic approach to addressing social determinants of adverse birth outcomes, are required.